Pre-rRNA processing and its response to temperature stress in maize. (31st October 2019) - Liu, Guoqin; Yan, Pengshuai; Du, Qingguo; Wang, Yafei; Guo, Yu; Fu, Zhiyuan; Wang, Hongqiu; Tang, Jihua
Abstract : Maize responds to temperature stress by modulating pre-rRNA processing, as evidenced by significant reductions of the levels of the P-A3 intermediate. Abstract: Ribosome biogenesis is a fundamental process in all eukaryotic cells and is coupled with the processing and maturation of pre-rRNAs. Maize is a primary staple crop across the world, but little is known about the exact pre-rRNA processing sites and pathways in this species. In this study, we present a detailed model of the pathway by identifying the critical endonucleolytic cleavage sites and determining the pre-rRNA intermediates by circular reverse-transcription PCR and northern blot analysis. We demonstrate that two pathways coexist in maize to promote the processing of 35S pre-rRNA, and that the processing of 27SA pre-rRNA can proceed via two different pathways, which are distinguished based on the order of ITS1 removal and ITS2 cleavage. Compared with yeast and mammals, this new 27SA pre-rRNA processing mechanism is unique to maize and other higher plants. In addition, we demonstrate that maize can modulate pre-rRNA processing levels in response to chilling and heat stress, as indicated by a significant reduction of the P-A3 intermediate. Our study provides information that will facilitate future research on ribosome biogenesis and pre-rRNA processing in maize.